Toward Cleaner Urban Air in South Asia: Tackling Transport Pollution, Understanding Sources - World Bank (World Bank, Washington, DC, 2014)
This ESMAP study was undertaken to provide technical input to support the region-wide process of developing and adopting cost-effective and realistic policies and efficient enforcement mechanisms to reverse the deteriorating trend in urban air quality in South Asia. It focused mainly on fine particulate matter, estimated to account for most premature mortality and illnesses caused by outdoor air pollution. Through stakeholder feedback, the study examined two areas where more information and policy analysis could complement ongoing activities on air pollution control: making vehicle emissions inspection more effective and understanding sources of small particulate matter. Poorly maintained older technology vehicles contribute disproportionately to total vehicular emissions. A common approach to identifying gross polluters and ensuring that they are repaired or retired is a vehicle inspection and maintenance (I/M) program. The analysis carried out in this study recommends that limited resources be concentrated on applying more robust (but also costly) test protocols to vehicle categories in large cities likely to contain a disproportionately large fraction of high annual-kilometer, gross polluters (for example, commercial diesel vehicles). The ultimate goal of I/M is to reduce human exposure to elevated concentrations of harmful pollutants. Where air pollution is not serious, the number of people exposed is not large, or for vehicles that are not driven many kilometers a year or do not pollute much (such as new gasoline vehicles), the benefit of testing vehicles would be much less limited, if not negligibly small.